(untitled) (The Review of Diabetic Studies, 2023)
Proinsulin C-peptide has been found to exert beneficial effects in many tissues affected by diabetic microvascular complications, including the kidneys. Glomerular hyperfiltration and microalbuminuria are early markers of diabetic nephropathy. C-peptide at physiological concentrations effectively reduces diabetes-induced glomerular hyperfiltration via constriction of the afferent arteriole, dilation of the efferent arteriole, and inhibition of tubular reabsorption in experimental models of type 1 diabetes. The glomerular hypertrophy and mesangial matrix expansion seen in early diabetes can be reduced or prevented by C-peptide administration, possibly via interference with TGF-β1 and TNFα signaling. Several of C-peptide’s reno-protective effects have been confirmed in human studies; reduced glomerular hyperfiltration and diminished urinary albumin excretion have been documented in type 1 diabetes patients receiving replacement doses of C-peptide for periods of up to 3 months. In this review, we critically summarize the current state of knowledge regarding C-peptide’s renal effects, and discuss possible mechanisms of its beneficial effects in diabetic nephropathy.